Dapatkah Pertimbangan Profesionalitas Meningkatkan Kualitas Kerja Karyawan? (Studi Ilmiah pada PT. Fajar Graha Pena Makassar) - Silvinus Charles Abar; Hasmin Tamsah; Warka Syachbrani (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2020)
This study aims to determine the effect of professional considerations on the quality of performance of employees at PT Fajar Graha Pena Makassar. This research is a quantitative research, by determining the sample using saturation techniques. The data collection techniques used were questionnaires, observation and documentation. Data analysis used simple linear regression analysis. The results of data analysis explain that considerations of professionalism have a positive and significant effect on the quality of performance of employees at PT. Fajar Graha Pena Makassar amounted to 61.80%.